DELIVERED BY WOMEN, LED BY WOMEN: THE FUTURE OF GLOBAL HEALTH LEADERSHIP. Issue 100 (18th June 2021) - Dhatt, Roopa; Keeling, Ann
Abstract: The authors note the disparity between leadership roles of men and women in global health and its effect on the response to COVID‐19. The work of their organization Women in Global Health is described, including "launching a Gender Equal Health and Care Workforce Initiative in 2021 in partnership with the Government of France and World Health Organization, convening governments and international organizations to leverage commitments for safe and decent work, equal pay and an equal say in leadership for women in health and social care." They note that women are "80 percent of the world's nurses and 90 percent of the frontline health workers." Yet the reality is that "women still deliver health systems led by men." The authors outline their vision for global health leadership; in brief, and in their words: First, we must change the narrative and see women as drivers of global health, not solely as users of health systems…. Second, women in health and social care need a new social contract… Third, COVID‐19 showed that viruses do not respect national borders and we live in an interconnected world… Fourth, beyond gender parity in global health leadership, we need leaders of all genders to be gender transformative leaders.